2011
DOI: 10.1063/1.3595940
|View full text |Cite
|
Sign up to set email alerts
|

Effective passivation of Si surfaces by plasma deposited SiOx/a-SiNx:H stacks

Abstract: Very low surface recombination velocities <6 and <11 cm/s were obtained for SiOx/a-SiNx:H stacks synthesized by plasma-enhanced chemical vapor deposition on low resistivity n- and p-type c-Si, respectively. The stacks induced a constant effective lifetime under low illumination, comparable to Al2O3 on p-type Si. Compared to single layer a-SiNx:H, a lower positive fixed charge density was revealed by second-harmonic generation measurements, while field-effect passivation was absent for a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…On lowly doped n-type Si, Al 2 O 3 generally passivates the surface well, as it induces strong near-surface inversion. However, inversion layers are associated with a lifetime reduction at low injection levels (Δn o10 15 cm À 3 ), which is within the operating regime of solar cells [13][14][15]. Secondly, besides affecting the surface passivation, inversion layers potentially act as undesired conduction pathways to metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…On lowly doped n-type Si, Al 2 O 3 generally passivates the surface well, as it induces strong near-surface inversion. However, inversion layers are associated with a lifetime reduction at low injection levels (Δn o10 15 cm À 3 ), which is within the operating regime of solar cells [13][14][15]. Secondly, besides affecting the surface passivation, inversion layers potentially act as undesired conduction pathways to metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…This significant positive-charge density leads to a strong inversion layer on the p-type c-Si surfaces, known as the "parasitic" or "inversion-layer shunting effect," leading to a reduction of the short-circuit current and cell efficiency [45]. SiO 2 /SiN x stacks are expected to reduce or nullify this detrimental effect [46,47].…”
Section: A-sin X :Hmentioning
confidence: 99%
“…An enhanced lifetime of the photon-generated carriers has also been realized using SiO 2 , SiN x , and SiCN x films as surface passivation layers [3][4][5]. Jana et al [6] showed the interface trap density (D it ) (2.52 × 10 11 cm −2 eV −1…”
Section: Introductionmentioning
confidence: 99%